Estudo antropométrico do idoso da amazônia para fins projetuais - PEDROSO, Ana Cristina Pacha de Carvalho (Universidade Federal do Pará, 2017)
There are investigated measures of upper limb reach from elderly Amazon for aims of conception of the architectural design that contribute to the knowledge of man’s specific anthropometric Amazon. The research develops in three stages considering anthropometry static, dynamic anthropometry and evaluation of normative NBR 9050 with seniors 60 years or older. The anthropometric measurements of static nature were taken by direct method with objective measures while the dynamic nature, were taken by indirect method with objective measures and filming of reaching movements. The obtained data were compared with those from other regions of Brazil. Finally, evaluate measures of Amazon regarding the technical parameters of the upper limbs reach that can subsidize the architectural design to contribute to discussion of the legislation in force. Brazil experience a major demographic shift related to the aging of its population age structure, with significant presence of persons aged 60 or more, for whom scientific knowledge needs new answers. The hypothesis that the measures for manuals reach predicted in the NBR 9050 are not suitable for the elderly Amazon is confirmed to reach on foot and not confirmed to reach sitting.